Evaluation of the safety and efficacy of herby angel tummy roll-on in managing infantile colic: a case series - Bajpai, Ajay; Ramamurthy, Swathi; Rao, Arpitha C. (International Journal of Contemporary Pediatrics, 2024)
Infantile colic is a benign condition of the second or third week of life characterized by abdominal discomfort. Infantile colic is characterized by persistent and unconsolable crying in an otherwise healthy and well-fed infant. About 20% of the newborn babies and infants are affected by this condition. This condition distress and challenges caregivers, leading to 10% to 20% of paediatric provider visits during the first few weeks of their lives. Current management options are limited and often involve oral administration which can be challenging for the caregivers. This study evaluated the safety and efficacy of the Herby Angel Tummy Roll-On, a topical treatment containing natural ingredients like Asafoetida, Ajwain, Rock salt, etc., designed to alleviate colic symptoms through a non-invasive approach. Four infants with recurrent colic episodes were monitored over one month, assessing improvements using the FLACC scale and other parameters such as frequency of interruptions, episodes of colic, and skin reactions. Significant improvements in symptoms were observed within a short duration, with no adverse skin reactions. The findings of this study suggest that the product effectively alleviated abdominal distension and pain, leading to a marked reduction in sleep disturbances in infants. It has a positive short-term effect on infantile colic.